2005
DOI: 10.1021/jp0531006
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Coordination Behavior of Cr3+ in Microporous Aluminophosphates

Abstract: A CrAPO-5 molecular sieve has been investigated with X-ray absorption spectroscopy (EXAFS-XANES) as dehydrated material and after loading with water and ammonia to unravel the coordination geometries of Cr 3+ in the framework of a microporous crystalline aluminophosphate, more particularly of the AFI-type. A comparison of the XANES data, a preedge analysis with crystal field multiplet calculations and EXAFS data, pointed toward the presence of framework Cr 3+ which, on dehydration, takes on a distorted tetrahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…Thus, a close vicinity of Cr 3+ ions to the lattice Al sites would lead to a shift of tetrahedral 27 Al line [40]. On the other hand, the possibility for the incorporation of Cr 3+ in the framework could not be excluded [16,21,25,26,31] as the framework incorporation of Cr 3+ in AlPO-5 was recently evidenced by the XAFS technique [32]. In addition, it is also supported by chemical analysis.…”
Section: +mentioning
confidence: 88%
See 2 more Smart Citations
“…Thus, a close vicinity of Cr 3+ ions to the lattice Al sites would lead to a shift of tetrahedral 27 Al line [40]. On the other hand, the possibility for the incorporation of Cr 3+ in the framework could not be excluded [16,21,25,26,31] as the framework incorporation of Cr 3+ in AlPO-5 was recently evidenced by the XAFS technique [32]. In addition, it is also supported by chemical analysis.…”
Section: +mentioning
confidence: 88%
“…À was an effective co-templating molecule for the framework incorporation of Cr when triethylamine and pseudo-boehmite were used as template and Al source respectively [25]. Incorporation of Cr 3+ ions in the framework of AlPO 4 -5 molecular sieves has recently been confirmed as well by X-ray absorption spectroscopy (EXAFS-XANES) [32], although it required the presence of two extra-framework oxygen atoms to complete its pseudo-octahedral coordination environment. Nevertheless, the general non-unity of the chemical compositions of Cr-containing samples indicates that among the studied transition metal ions, Cr 3+ is the most difficult one to be incorporated in the framework ( Table 1).…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] For the conventional Cr/ AlPO 4 -5, experimental evidence was found that the Cr is not incorporated in the framework, but rather is present as octahedral Cr III ions at the surface of the zeolite crystal. [15] However, it cannot be excluded that changing the synthesis conditions [16,17] might result in stable, supported, Cr-based autoxidation catalysts. The performance of recently discovered three-dimensional mesoporous chromium oxide in autoxidation reactions remains to be examined.…”
mentioning
confidence: 99%
“…Recently, Beale et al found the unusual coordination behavior of Cr 3+ in AFI via X-ray absorption spectroscopy (EXAFS-XANES). 11 They claimed that the Cr 3+ ion could be incorporated into the framework of AFI by replacing the Al 3+ ion and that the coordination geometry of Cr 3+ in dehydrated CrAPO-5 could take on a distorted tetrahedral coordination state. The coordination geometry of Cr 3+ could transform into 5-fold or 6-fold coordination in the presence of ammonia or water molecules.…”
Section: Introductionmentioning
confidence: 99%